2017
DOI: 10.3892/mmr.2017.7556
|View full text |Cite
|
Sign up to set email alerts
|

GPVI-Fc-PEG improves cerebral infarct volume and cerebral thrombosis in mouse model with cerebral thrombosis

Abstract: Cerebral thrombosis is one of the most common causes of cerebral infarction, and anticoagulation therapy is a routine treatment in patients with hemorrhagic cerebral venous thrombosis. The hemostatic function of platelets is important for the anticoagulation therapy of thrombosis. Glycoprotein VI (GPVI) is reported as the major signaling receptor for collagen and is exclusively expressed on platelets and megakaryocytes, initiating platelet recruitment at sites of vascular injury and demonstrating numerous bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…As we reported recently, FcγRIIA-stimulated platelet activation (aggregation, secretion, and P-selectin expression) and formation of platelet-neutrophil aggregates were completely suppressed by low concentrations of various Btk-inhibitors in vitro and by a single low oral dose of ibrutinib for several days ex vivo [13]. Further platelet-mediated mechanisms of vascular thrombosis, that are also blocked by Btk-inhibitors, are the activation of platelet glycoprotein (GP) VI by collagen exposed after endothelial injury and of GPIb by von Willebrand factor expressed on inflamed endothelium [14,15,16,17,18,19,20].…”
Section: Dear Sirmentioning
confidence: 99%
“…As we reported recently, FcγRIIA-stimulated platelet activation (aggregation, secretion, and P-selectin expression) and formation of platelet-neutrophil aggregates were completely suppressed by low concentrations of various Btk-inhibitors in vitro and by a single low oral dose of ibrutinib for several days ex vivo [13]. Further platelet-mediated mechanisms of vascular thrombosis, that are also blocked by Btk-inhibitors, are the activation of platelet glycoprotein (GP) VI by collagen exposed after endothelial injury and of GPIb by von Willebrand factor expressed on inflamed endothelium [14,15,16,17,18,19,20].…”
Section: Dear Sirmentioning
confidence: 99%
“…Other cases of a modified GPVI-Fc protein were observed in the study performed by Wufuer and collaborators, when GPVI-Fc was linked to polyethylene glycol (PEG), forming the protein GPVI-Fc-PEG (for a better pharmacological release). This molecule is associated with competitive blocking von Willebrand factor (VWF)–collagen interactions [ 118 ]. The administration of GPVI-Fc-PEG (0.18 mg per day) showed an increase in reperfusion and an improvement in the survival following cerebral thrombosis in a murine model, compared with treatment with GPVI alone and without the risk of intracranial bleeding [ 118 ].…”
Section: Advances In Gpvi Modulation By Antibodies and Inhibitory Pro...mentioning
confidence: 99%
“…This molecule is associated with competitive blocking von Willebrand factor (VWF)–collagen interactions [ 118 ]. The administration of GPVI-Fc-PEG (0.18 mg per day) showed an increase in reperfusion and an improvement in the survival following cerebral thrombosis in a murine model, compared with treatment with GPVI alone and without the risk of intracranial bleeding [ 118 ].…”
Section: Advances In Gpvi Modulation By Antibodies and Inhibitory Pro...mentioning
confidence: 99%
“…Hypertension is an important independent risk factor for cerebral infarction, which can directly cause a wide range of cerebral atherosclerosis (7,11). Thrombosis, which occurs on the basis of atherosclerosis, is one of the most common causes of cerebral infarction (24). It was reported that miR-155 was negatively correlated with elevated blood pressure by acting on the RAAS system.…”
Section: Mir-24 Decreased Serum Tc Tg and Hdl-c Levels In Mcao Modelmentioning
confidence: 99%